Kingdom of the Netherlands-Netherlands Antilles : Recent Developments, Selected Issues, and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
The paper provides a brief review of economic developments and policies in the Netherlands Antilles. The government's current adjustment initiative provides a much needed opportunity for restoring growth prospects for the Netherlands Antilles. The paper has looked into issues pertaining to the development and prospects of the Antillean offshore sector. The picture emerging is one of a sector that, after initial spectacular growth, has encountered a number of obstacles. Nevertheless, it has been able to continue to register positive, albeit more moderate, growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet